Evaluating Some Functional Properties of Surfaces with Partially Regular Microreliefs Formed by Ball-Burnishing - Volodymyr Dzyura; Pavlo Maruschak; Stoyan Slavov; Diyan Dimitrov; Volodymyr Semehen; Oleksandr Markov (Machines, 2023)
In the present work, functional properties of three different types of regular microreliefs, formed by ball burnishing process on flat surfaces are evaluated. For their estimation, heights and material ratio curve’s criteria were used, according to the international standard ISO 21920-2:2021. The influence of the regular relief’s type and ball burnishing process parameters on the surface functional properties were investigated using full factors experimental design. Based on the obtained results, statistical models were derived that describe the dependencies between the topography characteristics and the regular reliefs’ types and regime parameters of the ball burnishing process. Based on the obtained results, several conclusions have been formulated about the applicability of these standardized methods and criteria for evaluating the functional characteristics of the different types of regular reliefs at the end of the work.